Results of emergency salvage lung resection after chemo- and/or radiotherapy among patients with lung cancer. (7th March 2022) - Hino, Haruaki; Utsumi, Takahiro; Maru, Natsumi; Matsui, Hiroshi; Taniguchi, Yohei; Saito, Tomohito; Tsuta, Koji; Murakawa, Tomohiro
Abstract: OBJECTIVES: This study aimed to elucidate the outcomes of emergency salvage surgery following life-threatening events (serious haemorrhage and/or infections) among patients with lung cancer who had undergone chemo- and/or radiotherapy. Materials and Methods: We analysed the data of patient from 2015 to 2020, retrospectively. The clinical characteristics, including preoperative treatment, perioperative outcomes and survival time, were analysed. RESULTS: Of the 862 patients who underwent primary lung cancer surgeries, 10 (1.2%) underwent emergency surgeries. The preoperative clinical characteristics were: median age, 63.7 years [interquartile range (IQR) 55–70.5]; sex (male/female), 9/1; clinical staging before initial treatment (I/II/III/IV), 1/1/3/5; initial treatment (chemoradiotherapy/chemotherapy/proton beam therapy), 5/4/1; and indications for emergency surgery (lung abscess/lung abscess with haemoptysis/haemoptysis/empyema), 5/3/1/1. The selected procedures and results were as follows: lobectomy/bilobectomy/pneumonectomy, 8/1/1 (all open thoracotomies); median operation time, 191.0 min (IQR 151–279); median blood loss, 1071.5 ml (IQR 540–1691.5); postoperative severe complications, 3 (30%); hospital mortality, none; median postoperative hospital stay, 37 days (12–125); control of infection and/or haemoptysis, all the cases; final outcome (alive/dead), 3/7 (all the cancer deaths); median postoperative survival, 9.4 months (IQR 4.3–20.4); and median survival from initial treatment, 19.4 months (IQR 8.0–66.9). CONCLUSIONS: Emergency salvage lung resection is a technically challenging procedure; however, the results were feasible and acceptable when the surgical indication, procedure and optimal timing were considered carefully by a multidisciplinary team. Although the aim was palliation, some patients who received additional chemotherapy afterwards and, thus, had additional survival time. Abstract : Lung cancer is the leading cause of cancer-related deaths worldwide, including Japan [1].